Criminal Liability in Maritime Offenses Regarding Ship Accident Incidents - Nasution, Rahmat; Widjaja, Gunawan (CV. Publikasi Indonesia, 2025)
Indonesia as an archipelagic country places sea transportation as a vital means for national connectivity, population mobility, and the distribution of goods. In the context of the state of law, the handling of ship accidents should be subject to the provisions of laws and regulations, especially Law Number 17 of 2008 concerning Shipping as amended by Law Number 66 of 2024, Government Regulation Number 9 of 2019, and Regulation of the Minister of Transportation Number 6 of 2020. However, in practice, there is still a tendency for law enforcement officials to directly apply the provisions of the Criminal Code (KUHP), without prioritizing the mechanism of preliminary examination of ship accidents by Syahbandar or Ship Accident Inspectors (PKK) as stipulated in the Law on Shipping. This research is a normative legal research with an analytical descriptive approach. This study also aims to analyze the liability of shipping crimes for ship accidents, especially the application of the principle of lex specialis derogat legi generali between the Shipping Law and the Criminal Code, as well as the implementation of law enforcement in the case of the sinking of KMP ships. Tunu Pratama Jaya GT.792 in the Bali Strait.The results of the study show that, normatively, there is a clash of norms between two different regulations, namely between the Shipping Law and the Criminal Code. The analysis shows that the Shipping Law as a special rule based on the principle of lex specialis derogate legi generali is a rule that must take precedence in handling ship accident events, while the Criminal Code applies as a lex generalis which is subsidiary. The case of the KMP ship. Tunu Pratama Jaya shows the dualism of the examination and the potential for overlapping authority between Syahbandar/PPPK, PPNS Directorate General of Transportation and the Police, which has implications for legal uncertainty and the unenforced principle of ultimum remedium in law enforcement of shipping crimes.